Trend of viral load during the first, second, and third wave of COVID-19 in the Indian Himalayan region: an observational study of the Uttarakhand state - Negi, Shailender; Diksha,; Kalita, Deepjyoti; Ranakoti, Neeraj; Negi, Ashish; Kandwal, Diksha; Gupta, Shailesh Kumar; Mathuria, Yogendra Pratap (Frontiers in Microbiology, 2024)
India had faced three waves throughout the COVID-19 pandemic which had already impacted economic lives and affected the healthcare setting and infrastructure. The widespread impacts have inspired researchers to look for clinical indicators of SARS-CoV-2 infection prognosis. Cyclic threshold values have been used to correlate viral load in COVID-19 patients and for viral transmission. In view of this, a retrospective study was conducted to assess the trend of viral load in clinical and demographic profiles across the three waves. A total of 11125 COVID-19-positive patients data were taken which had a Ct value of <35. We stratified Ct values as: under 25 (high viral load), 25 to 30 (moderate viral load), and over 30(low viral load). We found a significantly high proportion of patients with high viral load during the second wave. In all three waves, a significantly high viral load across the symptomatic and vaccinated populations was found whereas a significantly high viral load across age groups was found only in the first wave. With the widespread availability of realtime PCR and the limited use of genomic surveillance, the Ct value and viral load could be a suitable tool for population-level monitoring and forecasting.